Targeted nutrition project at Muktagacha in Bangladesh: lessons learned - Chowdhury, A Mushtaque R; Hyder, S.M. Ziauddin; Mahmud, Zeba; Chowdhury, Sadia A. (BRAC Research and Evaluation Division (RED), 2019)
Millions of people suffer and many of them die from malnutrition in developing countries. BRAC, a non-governmental organisation in Bangladesh, has made significant progress towards planning and implementing nutrition programmes. Targeted nutrition interventions incorporated into programmes aimed at poverty alleviation significantly contribute to nutritional improvement.